Implementasi Metode Pembelajaran Syawir Dalam Meningkatkan Kompetensi Santri Pada Kitab Kuning Di Pondok Pesantren Nurul Hidayah Bandung-Kebumen - Janah, Miftakhul; Faisal, Faisal (IAINU Kebumen, 2025)
As time goes by, schools develop many learning methods to improve students' understanding and learning in absorbing lessons. In Islamic boarding schools, learning methods still use traditional methods, including syawir (discussion). The syawir method is an activity or way of learning to review the yellow book which has been taught by the ustadz in depth involving more than 2 people to produce a consensus together to discuss the rules of nahwu in reading the yellow book. This research uses a qualitative descriptive approach method. The research design is field research. Data was obtained from observations, interviews and documentation. Data processing techniques use data reduction, data presentation and drawing conclusions. The results obtained in the research are: the syawir activity is an activity of reviewing and understanding the yellow book in terms of reading and writing based on the rules of nahwu and shorof, the activity starts from 20.30 to 22.30 which includes three sessions, namely menembel, murodi and understanding, as well as concluding and asking questions. answer. The supporting factors are mustahiq's diligent work in supervising shawir activities and the students' curiosity about the latest subject matter. Meanwhile, the inhibiting factor is students who violate the rules, such as falling asleep during syawir activities. The solution is to impose sanctions on students who violate the rules and make syawir as interesting as possible so that students can quickly understand it